Gambaran Perilaku Hidup Bersih dan Sehat pada Tatanan Keluarga di Desa Cemparam Lama Kabupaten Bener Meriah - Juandi Rizki Ilhami; Cut Khairunnisa; Nina Herlina (Lembaga Pengembangan Kinerja Dosen, 2026)
Clean and healthy living habits (PHBS) is the essence and human right to maintain the continuity of life. Clean and healthy living habits is a set of behaviors that are practiced on the basis of awareness as a result of learning, which makes a person, family, group or community able to help themselves (independently) in the health sector and play an active role in realizing public health. The impacts of families who do not practice PHBS are numerous, this problem comes from unhealthy behavior and environments. Clean and Healthy Living Behavior in Cemparam Lama Village, Bener Meriah Regency, based on the results of observations made by the Mesidah District Health Center, Bener Meriah Regency, in 2022 is 1.8%. The aim of this research is to see the description of clean and healthy living behavior in the household structure in Cemparam Lama Village, Mesidah District, Bener Meriah Regency. This type of research is purely descriptive which aims to see the description of clean and healthy living habits in the family structure in Cemparam Lama Village, Bener Meriah Regency. Results of this research were good knowledge of respondents with a percentage of 93.9%, positive attitudes of respondents with a percentage of 95.6%, and good actions of respondents with a percentage of 94. 7%. Conclusion of this research is that the majority of families in Cemparam Lama Village, Mesidah District, Bener Meriah Regency have a good description of characteristics, knowledge, attitudes and actions regarding Clean and Healthy Living Habits.